2016
DOI: 10.1016/j.jvs.2016.03.409
|View full text |Cite
|
Sign up to set email alerts
|

Loss of kidney function in patients with critical limb ischemia treated endovascularly or surgically

Abstract: Endovascular procedures for critical limb ischemia are associated with clinically relevant permanent long-term loss of kidney function. This loss of renal function is greater than in comparable patients who were treated with open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Probably, the increased comorbidity, vessel calcification, and isolated below-knee atherosclerotic disease that are often present in CKD led the treating physicians to an endovascular-first approach. Of note, Sigterman et al 33 recently reported that endovascular revascularization is associated with greater loss of renal function compared with patients treated surgically. On the other hand, bypass surgery remained the treatment of choice for complex anatomical lesions despite numerous studies reporting on endovascular revascularization of TASC II C/D disease.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the increased comorbidity, vessel calcification, and isolated below-knee atherosclerotic disease that are often present in CKD led the treating physicians to an endovascular-first approach. Of note, Sigterman et al 33 recently reported that endovascular revascularization is associated with greater loss of renal function compared with patients treated surgically. On the other hand, bypass surgery remained the treatment of choice for complex anatomical lesions despite numerous studies reporting on endovascular revascularization of TASC II C/D disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic and abdominal aortic procedures (endovascular as well as open surgical repair (OSR)) carry a higher risk of AKI than peripheral vascular operations. Peripheral vascular procedures have some of the lowest rates, from 4% for patients undergoing infrainguinal lower extremity bypass, up to 19% for endovascular revascularization of critical limb ischemia [26,[30][31][32].…”
Section: Risk Factors Of Post-contrast Akimentioning
confidence: 99%
“…In addition to increasing risk of mortality and amputation, CKD also increases the failure rate of endovascular/revascularization surgical interventions in PAD 3,12,13 . Complicating the mortality and surgical failure risk, administration of contrast dyes during endovascular/revascularization surgeries has been shown to induce acute kidney injury that increases future risk of developing CKD 14,15 . Despite strong epidemiological data linking CKD to worsened PAD health outcomes, the biological mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%